Decentralized dynamic power control in an islanded DC microgrid with hybrid energy storage system - Sharmila Nagaraju; Narataj Kanathur Ramaswamy (Institute of Advanced Engineering and Science, 2022)
The integration of renewable energy resources to utility grid calls for selection of suitable storage system to store generated energy with reliable supply of demand and selection of efficient control system for smooth control of the grid. Battery is the most common energy storage system. Combining a supercapacitor to it makes the system performance better during transients. This paper proposes a hybrid energy storage system with a battery and a supercapacitor to reduce transient power fluctuations and improve the life span of the battery by reducing the charging/discharging cycles with the incorporation of supercapacitor. The battery compensates constant power fluctuations whereas the supercapacitor compensates the transient power fluctuations. This system design offers improved performance, with better regulation of dc link voltage, frequency regulation compared to microgrid with single energy storage. The dynamic performance of the system under varying load conditions has been improved. The work proposes the power management algorithm, which helps in efficient monitoring and smooth control of the entire system. Integration of supercapacitor to the storage system enhances the performance of the microgrid, increases life span of battery and reduces the stress on battery. The DC link bus voltage is efficiently regulated and the demand is supplied reliably.